Modul Pembelajaran Biologi SMA Berbasis Riset Struktur Vegetasi di Lahan Gambut Pasca Kebakaran - Nursal, Nursal; Fauziah, Yuslim; Firdaus, L.N.; Amran, Afitria (Indonesian Biology Teachers, 2018)
Abstract. Many peatland fires have a negative impact on the natural ecosystem, one of them on plants. This study aims to produce high school biology learning modules by utilizing the results of studies on the regeneration of plant vegetation in peatlands after the fire. To achieve these objectives, a survey study was conducted in Rimbo Panjang Village, Kampar District, Riau Province in February-October 2017. Quadratic method and sampling technique by purposive random sampling were applied to gradient of fire incident 2009, 2013, 2014, 2015, 2016 and 2017. Data were analyzed descriptively-qualitative. The results show that the pot-fire peatland vegetation  structure of  Rimbo Panjang contains  9 families . Diversity index  of trees was  0.29, sapling  were 0.37 and the seedling were 0.6. Modules developed based on the results of this study can be used as a source of learning subjects Biology high school class X on Ecosystem Components (KD 3.10) and the impact on environmental changes (KD 3.11). However, the design of this module needs to be tested before it is applied and the students learning is classical. Keywords: Biology instructional modul, Senior High School, Vegetation Structure, Post-fire peatland.